Problem-Based Learning dalam Pembelajaran Sistem Persamaan Linear Dua Variabel - Iswanto (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2022)
The purpose of this study was to describe the ability of mathematics problem solving of junior high school students through Problem-Based Learning in SPLDV. The type of research is qualitative descriptive study. Subjects in this study were students of SMP Negeri 2 Toboali VIII.2. This study used problem-solving-consisted scoring guidelines: understand the problem, plan problem-solving strategies, carry out troubleshooting, and recheck the settlement. The results of this study indicate that the students are able to solve mathematical problems for junior high school level through Problem-Based Learning in SPLDV learning in class VIII SMP Negeri 2 Toboali. Therefore, Problem-Based Learning strategy can be used as an alternative to conduct of mathematics learning in junior high school.